Unfolding molecular switches for salt stress resilience in soybean: recent advances and prospects for salt-tolerant smart plant production - Feng, Chen; Gao, Hongtao; Zhou, Yonggang; Jing, Yan; Li, Senquan; Yan, Zhao; Xu, Keheng; Zhou, Fangxue; Zhang, Wenping; Yang, Xinquan; Hussain, Muhammad Azhar; Li, Haiyan (Frontiers in Plant Science, 2023)
The increasing sodium salts (NaCl, NaHCO3, NaSO4 etc.) in agricultural soil is a serious global concern for sustainable agricultural production and food security. Soybean is an important food crop, and their cultivation is severely challenged by high salt concentration in soils. Classical transgenic and innovative breeding technologies are immediately needed to engineer salt tolerant soybean plants. Additionally, unfolding the molecular switches and the key components of the soybean salt tolerance network are crucial for soybean salt tolerance improvement. Here we review our understandings of the core salt stress response mechanism in soybean. Recent findings described that salt stress sensing, signalling, ionic homeostasis (Na+/K+) and osmotic stress adjustment might be important in regulating the soybean salinity stress response. We also evaluated the importance of antiporters and transporters such as Arabidopsis K+ Transporter 1 (AKT1) potassium channel and the impact of epigenetic modification on soybean salt tolerance. We also review key phytohormones, and osmo-protectants and their role in salt tolerance in soybean. In addition, we discuss the progress of omics technologies for identifying salt stress responsive molecular switches and their targeted engineering for salt tolerance in soybean. This review summarizes recent progress in soybean salt stress functional genomics and directs future challenges and the way forward for molecular breeding of salt tolerant soybean.